Cutting too close? Design protection and innovation in fashion goods - Petal Jean Hackett (Center for Economic Studies and ifo Institute (CESifo), 2012)
Continued lobbying by high-end, American designers for intellectual property-type fashion design protection has culminated in the proposed Innovative Design Protection and Piracy Prevention Act, intended to introduce EU standards. Using a sequential, 2-firm, vertical differentiation framework, we analyze the effects of protection on investment in innovative designs by high-quality (designer) and lower-quality (mass-market) firms when the mass-marketer may opt to imitate, consumers prefer trendsetting designs and firms compete in prices. We show that design protection, by transforming mass-marketers from imitators to innovators, may reduce both designer profits and welfare. The model provides possible explanations for the dearth of EU case law and the increase in designer/mass-marketer collaborations.
Keywords: D21; L13; O31; O34; 330; intellectual property rights; fashion design protection; imitation; licensing; Mode; Produktdesign; Immaterialgüterrechte; Wirkungsanalyse; Bekleidungsindustrie; Innovation; Imitationswettbewerb; Wohlfahrtseffekt; Theorie; EU-Staaten